Training programme impact in improving the working memory of students with learning disabilities in reading arabic - Khalid Mohammad Aljundi (Journal of Education and Learning (EduLearn), 2020)
The study aimed to investigate the effect of a training program on improving working memory for students with learning difficulties in reading Arabic. The study sample consisted of (10) students with learning disabilities from Basic Education students from the fifth and sixth grades, and those between the ages (10-11) years as a pilot group and (10) students from the same stage and of the same age as a control group. The researcher used a working memory battery, Raven Test, and a training program he prepared to achieve the study goal. The results showed that there are statistically significant differences in the fields of working memory scale between the members of the experimental and control groups in the dimensional measurement, and in favor of the experimental group to which the training program was applied, by applying the measure of working memory in its three fields. The results also showed that there are statistically significant differences between the pre and post measurements of the areas of the working memory scale in favor of the post application, and for the benefit of the experimental group,This confirms the effectiveness of the training program used. Some recommendations were suggested.